(untitled) (Journal of Engineering, 2025)
Predicting Stream flow forecasting is of great interest to engineers and hydrologists for the management and planning in designing water resources projects and for water resources for. Long-term and short-term stream flow forecasting can provide valuable information on the possibility of designing water projects. This paper aims to improve the hydraulic performance selected channel namely the Shatt al-Ibrahim channel by measuring the depth of flow, using an Inflatable dam and comparing it with the water depth before the dam was placed in operational discharge (2 m3/sec). One-dimensional and two-dimensional numerical models are generated and analyzed using HEC-RSA software and then calibration with a physical model. The study results included a rise in water depth upstream of the inflatable dams compared to the natural case of almost 1.32 m in the dam region and 0.16 m at the beginning of the channel and backwater curve extends from 18 kilometers to zero kilometers and the velocity of water in downstream is not effect to the bed of channel and it doesn’t happen to scour in concrete, The calibration results between the numerical model and the physical model by using the coefficient of determination R2 (the acceptable value it is closer to 1).